MAIN PRINCIPLES FOR DEVELOPING READING SKILLS IN ESL/FL CLASSROOMS - Nani Hizriani (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
Reading is an essential skill for ESL/FL learners because it is a readily available way to expose to language learners’ target language. The ability to read in a foreign language is needed as the learners have specific needs for information and pleasure, for their career and for study purposes. Good reading texts provide a number of educational objectives and can bring in interesting topics, stimulate discussion, debate and motivate imaginative responses and can be the springboard for fascinating lessons. This study provides a framework for a series of key principles for developing reading skills and explain how these principles can be applied in the ESL/FL classroom.